2013
DOI: 10.1002/ardp.201300097
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Bis‐Imidazolidineiminothiones: A Comparative Study

Abstract: A series of 15 novel symmetrical and non-symmetrical bis-imidazolidineiminothiones (6a-g, 7a-e, 8a,b, and 9) with various substituents at N-(1) (p-tolyl, p-methoxyphenyl, p-ethoxyphenyl, p-chlorophenyl, p-bromophenyl, p-iodophenyl, and 3,5-dichlorophenyl) and different linkers between the N-(3) atoms [4,4'-oxybis(4,1-phenylene), 2,2'-dimethoxybiphenyl, and (1,3,3-trimethylcyclohexyl)methyl)] were prepared in 65-75% yields from substituted N-arylcyanothioformanilides and various bis-isocyanates. Screening for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 61 publications
3
18
0
Order By: Relevance
“…The 1 H NMR spectra of compounds 2a-c exhibited two singlet signals around δ 8.60 (C=NH) and 9.60 ppm (NH imidazole ring) along with aromatic protons. 13 C NMR spectra of compounds 2b,c displayed signals at δ 187.8-188.2 ppm due to C=S. The reaction mechanism was assumed to proceed through a nucleophilic attack of the nitrogen atom of the cyanothioformamide moiety (1a) to the cyano group in arylhydrazonomalononitrile to form intermediate that followed by intramolecular cyclization to yield the cyclized products 2 as illustrated in Scheme 1.…”
Section: Chemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…The 1 H NMR spectra of compounds 2a-c exhibited two singlet signals around δ 8.60 (C=NH) and 9.60 ppm (NH imidazole ring) along with aromatic protons. 13 C NMR spectra of compounds 2b,c displayed signals at δ 187.8-188.2 ppm due to C=S. The reaction mechanism was assumed to proceed through a nucleophilic attack of the nitrogen atom of the cyanothioformamide moiety (1a) to the cyano group in arylhydrazonomalononitrile to form intermediate that followed by intramolecular cyclization to yield the cyclized products 2 as illustrated in Scheme 1.…”
Section: Chemistrymentioning
confidence: 99%
“…Also, 1 H NMR spectra showed another specific broad signal around δ 9.42 ppm for NH proton. 13 C NMR spectrum of compound 3b displayed four signals at δ 13.5, 19.3, 20.8 and 29.0 ppm for butyl carbons, three signals at δ 153.8, 154.6 and 183.1 ppm for C=N, C=O and C=S, respectively. 5-Imino-5-thioxo-2-imidazolidinone derivatives (3a-c) were furnished as the sole products, indicating that the ring closing reaction proceeds via a single path, which involves attack via the nitrogen atom.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, N ‐arylcyanothioformamide reagents have found many applications in synthetic organic chemistry. The use of such reagents in heterocyclic chemistry has been nicely showcased by many researchers in the synthesis of otherwise inaccessible plethora of highly bioactive heterocyclic compounds, drug targets, and natural products such as luciferin . Although cyanothioformamides were first reported in 1904 and have been extensively used ever since, their full synthetic potential is still being established and several research groups around the globe are still aggressively pursuing such endeavour as demonstrated by the recent surge of research articles published by various groups on a wide range of transformations mediated by such reagents ( vide infra ).…”
Section: Introductionmentioning
confidence: 99%